A prospective real‐world study evaluating serum levels of arginine and cysteine in women with chronic telogen effluvium: do we really need blanket prescription of amino acid supplementation?. (12th September 2022) - Arora, Damini; Arora, Pooja; Goyal, Parul; Paliwal, Purnima; Sardana, Kabir
Abstract: Amino acids form a major component of hair fibres and are prescribed routinely in the form of nutritional supplements in patients with chronic telogen effluvium (CTE). Such a practice is based on assumption of a nutritional deficiency state in such patients. In this prospective study, we evaluated the serum levels of cysteine and arginine in 30 women with CTE and in healthy controls. We found no significant difference between the two groups in terms of serum arginine levels. Cysteine levels were higher in patients with CTE ( P  < 0.001). No correlation was found between levels of serum amino acids (cysteine and arginine) and either diet type (vegetarian or not) or body mass index, and no significant correlation between levels of the two amino acids and severity of disease. Our work suggests that arginine and cysteine deficiency is not present in women with CTE. Supplementation is unlikely to be of any benefit in nutrient‐replete populations and only adds to the cost of therapy. Abstract : Amino acids form a major component of hair fibres and are prescribed routinely as nutritional supplements in patients with chronic telogen effluvium (CTE), under the assumption of a nutritional deficiency states. We evaluated serum levels of cysteine and arginine in 30 women with CTE and healthy controls. We found no significant difference in serum arginine levels between the two groups, but cysteine levels were actually higher in women with CTE compared with controls. There was no significant correlation between serum amino acid levels and either diet type or body mass index, or between levels of micronutrients and disease severity. This study suggests that deficiency of either arginine or cysteine is not seen in women with CTE. Supplementation is unlikely to be of any benefit in nutrient‐replete populations and adds to therapy costs.